2013
DOI: 10.1002/jbmr.1899
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the development of vertebral fractures after percutaneous vertebroplasty

Abstract: We have recently observed an increased risk for vertebral fractures (VF) in a randomized controlled trial comparing the analgesic effect of vertebroplasty (VP) versus conservative treatment in symptomatic VF. The aim of the present study was to evaluate the risk factors related to the development of VF after VP in these patients. We evaluated risk factors including age, gender, bone mineral density, the number, type, and severity of vertebral deformities at baseline, the number of vertebral bodies treated, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…After reviewing the full text of the remaining 26 studies, we excluded nine additional full‐text articles. Finally, 17 unique studies with sufficient data were included and analysed in the meta‐analysis . A flow diagram that shows the literature search process is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reviewing the full text of the remaining 26 studies, we excluded nine additional full‐text articles. Finally, 17 unique studies with sufficient data were included and analysed in the meta‐analysis . A flow diagram that shows the literature search process is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The descriptive statistics for the studies that were included in our meta‐analysis are summarized in Table . Of the studies, eight were conducted in China, six were conducted in Korea, one was conducted in the Netherlands, one was conducted in Japan and one was conducted in Spain . The results of the quality assessment are summarized as follows: two studies received a score of 9, eight studies received a score of 8, five studies received a score of 7 and two studies received a score of 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of different inclusion criteria, studies have reported the risk of an adjacent fracture after PVP may increase with a lower BMD (6,(16)(17)(18), greater age (16,19), female gender, and cement leakage to disc (19,20), intervertebral vacuum (16), lower BMI (21), increased preoperative segmental kyphosis (22), greater anterior height restoration rate (18), the distribution of cement within the fracture (23) and a larger number of fractures (17,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Intradiscal cement leakage (ICL) has been associated with each of the Tome-Bermejo categories in new adjacent and non-adjacent vertebral compression fractures. Pain with this leakage can reduce the quality of patients' lives (22)(23)(24)(25)(26). The risk factors for ICL are still under debate (19,(27)(28)(29).…”
Section: Radiographic Evaluation and Data Collectionmentioning
confidence: 99%